(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article states the methodology of using innovative technologies in teaching listening comprehension in English classes and approaches of developing listening skills. The author emphasizes some criteria to develop listening skills and create some methods.